Handbook of polymer applications in medicine and medical devices - Modjarrad, Kayvon; Ebnesajjad, Sina; ScienceDirect eBooks (Oxford : Elsevier/William Andrew, 2014)
While the prevalence of plastics and elastomers in medical devices is now quite well known, there is less information available covering the use of medical devices and the applications of polymers beyond medical devices, such as in hydrogels, biopolymers and silicones beyond enhancement applications, and few books in which these are combined into a single reference. This book is a comprehensive reference source, bringing together a number of key medical polymer topics in one place for a broad audience of engineers and scientists, especially those currently developing new medical devices.
Introduction / Kayvon Modjarrad -- Application of plastics in medical devices and equipment / Len Czuba -- Plastics used in medical devices / Laurence W. McKeen -- Polymeric biomaterials / Roberto Benson -- Biofilms, biomaterials, and device-related infections / Sandeep Kathju -- Adhesives for medical and dental applications / Sina Ebnesajjad -- Silicones / Jim Curtis -- Review of research in cardiovascular devices / Zbigniew Nawrat -- Endotracheal tube and respiratory care / Jeffrey P. Keck Jr. -- Applications of polyaryletheretherketone in spinal implants: fusion and motion preservation / Steven M. Kurtz -- Microbubble applications in biomedicine / John R. Eisenbrey -- Hydrogels in regenerative medicine / David F. Williams -- Biodegradable polymers / Joachim Kohn -- Regulations for medical devices and application to plastics suppliers: history and overview / Vinny R. Sastri.
Includes bibliographical references and index.
Online resource; title from resource home page (ebrary, viewed on January 20, 2015).
Elsevier
Keywords: Polymers in medicine; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Polymers in medicine; Polymers -- therapeutic use; Biocompatible Materials -- chemistry; Biocompatible Materials -- therapeutic use; Equipment Design; Polymers -- adverse effects; Polymers -- chemistry; Electronic books